(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2026)
In the context of a contemporary culture of images, this study reflects on the possibilities of using image projections in theatrical performance. As these concepts emerge from new audiovisual resources driven by technological advancements, it becomes necessary to define the types of media present in contemporary theatre and the related terms, such as remediation, immediacy, hypermediacy, and intermediality. To illustrate these concepts, we analyze productions such as King of War, by Ivo Van Hove; Le Projet Andersen, by Robert Lepage; and Eraritjaritjaka, by Heiner Goebbels. Finally, the study seeks to provide analytical support for investigating new possibilities within media theatre.